2001
DOI: 10.1016/s0969-2126(01)00645-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Dehydrogenase

Abstract: Analysis of the crystal structures of the free enzyme and of the binary complexes with NAD(+) and glycerol show that the active site of GlyDH lies in the cleft between the enzyme's two domains, with the catalytic zinc ion playing a role in stabilizing an alkoxide intermediate. In addition, the specificity of this enzyme for a range of diols can be understood, as both hydroxyls of the glycerol form ligands to the enzyme-bound Zn(2+) ion at the active site. The structure further reveals a previously unsuspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 49 publications
5
84
1
1
Order By: Relevance
“…The fold of TM0423 was predicted by FFAS (24) to be similar to that of dehydroquinate synthase from Aspergillus nidulans (25) with a Z score of 52. The recently published structure of the Bacillus stearothermophilus glycerol dehydrogenase (26) provided an even better model for TM0423, but was not available for molecular replacement at the time of data collection. In all, five native TM0423 crystals were screened.…”
Section: Resultsmentioning
confidence: 99%
“…The fold of TM0423 was predicted by FFAS (24) to be similar to that of dehydroquinate synthase from Aspergillus nidulans (25) with a Z score of 52. The recently published structure of the Bacillus stearothermophilus glycerol dehydrogenase (26) provided an even better model for TM0423, but was not available for molecular replacement at the time of data collection. In all, five native TM0423 crystals were screened.…”
Section: Resultsmentioning
confidence: 99%
“…4). Recently, the crystal structure of coenzyme NAD ϩ -dependent glycerol dehydrogenase (GlyDH) of Bacillus stearothermophilus was solved (32). This protein, which is 23% identical and 40% similar to MDH, partly contains the conserved motif A of family III ADHs, but with a Lys residue at the position of the Ser 97 residue of MDH.…”
Section: Resultsmentioning
confidence: 99%
“…The three-dimensional structure of the glycerol dehydrogenase protein of Bacillus stearothermophilus revealed that the nicotinamide group of its coenzyme NAD ϩ binds in a deep pocket formed by nine amino acid residues (32). In MDH, which is 23% identical and 40% similar to glycerol dehydrogenase, this pocket is also present; of these nine amino acid residues, six residues are identical and three are similar.…”
Section: Act-mediated Hydrolysis Of Mdh-bound Nad(h) Cofactor-the Datmentioning
confidence: 99%